Pattern of Use of Antibiotic at Community Level in Under 5 Years of Age: A Descriptive Type of Cross Sectional Study - Chowdhury, Rana; Barua, Tanuka; Aktar, Feroza; Morshed, Monzur; Amin Chowdhury, Muhammad Jabed Bin; Chowdhury, Priyanka (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Antibiotic resistance is becoming a great problem/major threat worldwide regarding/contributing disease mortality and morbidity. In our country reveled that prevalence of antibiotic resistance for most common organism is quite high and many of the common first-line drugs were mostly ineffective. Though antibiotic resistance may occur naturally over time due to genetic mutation but misuse and overuse of antibiotics plays a great role for emergence of resistance. The objective of the study to find out the pattern of use of antibiotic at community level by different level of physician. Materials and methods: The study was designed as a descriptive type of study conducted in the Outpatient Department of Chattagram Maa Shishu O General Hospital, a tertiary care hospital from 1 st September 2022 January – 28 th February 2023.The study population was 350 patients age from 29 th days to 5 years who receive antibiotic at community level. Results: A total of 350 children of 29 days to 5 years of both sexes who prescribed antibiotic at community were enrolled in this study. Within the study group , 56% cases antibiotic advised by MBBS doctor rest are by nonregistered doctor and 38% patient took antibiotic in inadequate dosage and duration. 62% patient prescribed antibiotic without investigation. Most commonly prescribed antibiotic was Cefixime and most common disease Symptoms is fever and cough, cough and running nose. Conclusion: The common cause of antibiotic resistance is use without indication, inappropriate dosage and duration. At community level most of the physician does not follow the antibiotic guide line. So Govt. and health professional should take proper step to create awareness about antibiotic resistance. JCMCTA 2023 ; 34 (2) : 14-18